2012
DOI: 10.1182/blood.v120.21.3440.3440
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Megakaryocyte Differentiation Drives Nuclear Accumulation and Transcriptional Function of MKL1 Via Actin Polymerization and RhoA Activation

Abstract: 3440 Background: How components of the cytoskeleton regulate complex cellular responses is fundamental to understanding cellular function. Megakaryocyte Leukemia 1 (MKL1), an activator of serum response factor (SRF) transcriptional activity, plays critical roles in muscle, neuron, and megakaryocyte differentiation. Regulation of MKL1 subcellular localization is one mechanism by which a cell can control SRF activity with MKL1 localization to the nucleus being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Although some of these genes, such as CD41 and CD61, were already expressed by untreated HEL cells, TPA induction (both with and without MRTFA OE ) induced upregulation of ;200 Mk-associated genes, including VWF, KALRN, GFI1B, MYLK, FYN, GP1BB, GP5, GP9, SELP, and TBXA2R (genes upregulated in both TPA-induced HEL cells and in primary human cells are listed in supplemental Table 4). Promoter motif analysis 19 of the these genes indicated that many could be regulated by ETS factors, consistent with published data suggesting that TCFs, including ETS proteins, 26 play a role in TPA-induced gene activation in fibroblasts. 18 GO revealed enrichment for genes involved in integrin and receptor binding, which are important for Mk maturation and subsequent platelet formation.…”
Section: Mrtfa Oe Retains Srf Binding At Carg Sitessupporting
confidence: 88%
See 3 more Smart Citations
“…Although some of these genes, such as CD41 and CD61, were already expressed by untreated HEL cells, TPA induction (both with and without MRTFA OE ) induced upregulation of ;200 Mk-associated genes, including VWF, KALRN, GFI1B, MYLK, FYN, GP1BB, GP5, GP9, SELP, and TBXA2R (genes upregulated in both TPA-induced HEL cells and in primary human cells are listed in supplemental Table 4). Promoter motif analysis 19 of the these genes indicated that many could be regulated by ETS factors, consistent with published data suggesting that TCFs, including ETS proteins, 26 play a role in TPA-induced gene activation in fibroblasts. 18 GO revealed enrichment for genes involved in integrin and receptor binding, which are important for Mk maturation and subsequent platelet formation.…”
Section: Mrtfa Oe Retains Srf Binding At Carg Sitessupporting
confidence: 88%
“…In the MRTFA OE group without TPA treatment, the intensities of peaks for both binding categories (ie, increased and decreased SRF binding) were similar to those of the untreated control group, consistent with the cytoplasmic localization of MRTFA in the absence of TPA. 19 When comparing the peaks from cells treated with TPA, the peak for normalized reads for increased binding was much higher in the MRTFA OE TPA 1 group, indicating that MRTFA OE enhanced the TPA-induced association of SRF with these genomic regions. For those regions with decreased SRF binding in response to TPA, there was in contrast very little change between untreated and MRTFA OE TPA 1 groups, indicating that MRTFA OE may prevent SRF from being dislodged.…”
Section: Mrtfa Oe Increases Srf Binding To the Genome During Mk Maturationmentioning
confidence: 94%
See 2 more Smart Citations
“…TIPE2 has been found to reduce F-actin polymerization and to inhibit cell migration (18). As actin polymerization is essential for the nuclear translocation of RhoA and protein trafficking (35,36), the effects of TIPE2 on MMP expression and cell migration might be due to the modulation of F-actin polymerization and epithelial-mesenchymal transition by TIPE2. In this study, we demonstrate that TIPE2 inhibits the effect of TNF-α on Erk1/2-NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%